درجة مساهمة الحاسب الآلي في تطوير جودة الإدارة المدرسية - جلاب, مصباح; خطوط, رمضان (جامعة الوادي - University of Eloued, 2019)
هدفت الدراسة إلى التعرف على درجة مساهمة الحاسب الآلي تطوير جودة الإدارة المدرسية. والتعرف على درجة مساهمة الحاسب الآلي تطوير جودة العملية التعليمية. للتحقق من واقع استخدام الحاسب الآلي في المدرسة الجزائرية. وقد طرحنا التساؤل العام: ما هي درجة مساهمة الحاسب الآلي في تطوير جودة الإدارة المدرسية والعملية التعليمية التعلمية؟ وقد استخدم الباحثان المنهج الوصفي التحليلي، على عينة من 80 مديرا ومعلما، تم اختيارهم بطريقة قصدية، وأداة عبارة عن استبيانين يتكون الأول من 17 عبارة. والثاني من 13 عبارة. يتم الإجابة عنها وفق ثلاثة بدائل هي: بدرجة كبيرة (3)، بدرجة متوسطة (2)، بدرجة ضعيفة (1). كما اعتمد الباحثان في حساب الثبات على طريقة التطبيق وإعادة التطبيق بفاصل زمني قدره اسبوع على عينة استطلاعية من 20 فردا، وباستخدام معامل الارتباط بيرسون كانت النتيجة 92%، وبذلك يكون الصدق الذاتي 0.95. وباستخدام الأساليب الإحصائية المناسبة، توصلت الدراسة إلى النتائج التالية: 1- يساهم الحاسب الآلي بدرجة كبيرة في تطوير جودة الإدارة المدرسية بنسبة 84.19%. 2- يساهم الحاسب الآلي بدرجة كبيرة في تطوير جودة العملية التعليمية التعلمية بنسبة 88.07%.ABSTRACT:The study aimed to identify the degree of computer contribution to the development of the quality of school administration. And to identify the degree of computer contribution to improve the quality of the educational process. Check the reality of the use of computers in the Algerian school. We asked the general question: What is the degree of the computer's contribution to the development of the quality of school administration and the educational learning process? The researchers used the descriptive analytical approach on a sample of 80 principals and teachers, which were deliberately selected, and a tool consisting of two questionnaires consisting of 17 items. The second of 13 items. It is answered by three alternatives: high (3), medium (2), low (1). Researchers in the calculation of stability in the period between December 10, as adopted on tests and retest one week on a prospective sample of 20 people using the result of the Pearson correlation coefficient was 92%, so personal honesty is 0.95. Using the appropriate statistical methods, the study found the following results: IT contributes significantly to the quality of school management of 84.19%. The computer greatly contributes to the development of a quality educational learning process of 88.07%.
مقال
Keywords: الحاسب الآلي; الجودة; الإدارة المدرسية; العملية التعليمية التعلمية; computer; quality, school administration; learning process